Virtual is so real! Consumers' evaluation of product packaging in virtual reality - Branca, G.; Resciniti, R.; Loureiro, S. M. C. (Psychology and Marketing, 2023)
Virtual Reality (VR) is shaping all human activities, and with the advent of the metaverse, buyers are going to experience new ways of doing shopping. What would happen if consumers will be asked to assess a product's attribute, i.e., packaging, in a virtual environment, instead of being able to physically hold the product, like in a traditional purchasing process? The aim of this study is to analyze consumers' evaluation of packaged products in immersive VR, manipulating packaging structural and haptic cues, and clarify potential differences with the consumers' responses in the real life. We conducted two focus groups (Study 1), with 16 participants, a mixed design experiment (Study 2), involving 167 consumers, to analyze consumers' attitudes, and a choice-based conjoint analysis (Study 3), with 41 individuals, to study actual choice behavior. The main findings reveal that consumer behavior in VR is consistent with everyday life, except for minor variations. VR proves to be an efficient and rigorous research environment, also suitable for testing sensory cues and non-tangible attributes. Finally, the article suggests managers can effectively use VR for product and packaging development, through a more sustainable process that requires fewer resources and time compared to traditional tests